Penerapan Media Sica Box dalam Meningkatkan Pemahaman Siswa Pada Materi Sifat-Sifat Cahaya Kelas V SD Plus Melati Samarinda - Marniati Kadir; Nia Isnaniatun; Rima Rahma Dani (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aimed to improve students' understanding of the properties of light through the implementation of SICA Box learning media in Grade V students of SD Plus Melati Samarinda. The research employed Classroom Action Research (CAR) conducted in two cycles. Each cycle consisted of planning, action, observation, and reflection stages. The subjects were 20 fourth-grade students. Data were collected through observation, tests, and documentation. The results indicated that the implementation of SICA Box significantly improved students' understanding of the properties of light. Learning mastery increased from 45% in the pre-cycle to 70% in Cycle I and reached 90% in Cycle II. Students' learning activities also showed substantial improvement throughout the learning process. Therefore, SICA Box is effective in improving students' understanding of the properties of light.